BIOCHAR AMENDMENT IN BENZO[A]PYRENE CONTAMINATED SOIL FOR BIOREMEDIATION OF POLLUTED SOIL - Sushkova, Svetlana; Chaplygin, Viktor; Minkina, Tatiana; Popileshko, Jana; Antonenko, Elena (International Multidisciplinary Scientific GeoConference SGEM, 2018)
The aim of this article is assessment biochar bioremediation potential in the benzo[a]pyrene artificially contaminated Haplic Chernozem with various doses of benzo[a]pyrene (200, 400 and 800 µg/kg) equivalent to 10, 20 and 40 levels of maximal permissible concentrations (MPC) and 1-5% biochar amendment. The main subject of this study is to research the most effective dose of biochar amendment in benzo[a]pyrene contaminated soil in a model experiment with chernozem. The content of benzo[a]pyrene in soil was determined by using new ecologically friendly method of subcritical water extraction instead of traditional methods based on a large amount of organic solvents. The experiment was carried out with Haplic Chernozem, virgin, taken from the upper 0-20 cm layer of soil in the State Soil Preserve "Persianovsky preserved steppe" of Rostov region (south of Russian Federation) located far from contaminated sources. This soil revealed the following physical and chemical characteristics: Corg 3.4%; pH 7.3; cation exchange capacity (CEC) 37.1 mMol(+)/100g; content of CaCO3 0.1%; physical clay 53.1% and clay 32.4%. The experimental soil samples were incubated outdoor during 4 months. The express-method of subcritical water extraction was used for benzo[a]pyrene extraction from samples. Thus, the influence of different doses of biochar was revealed on the dynamics of benzo[a]pyrene content in soils. The influence of natural and technogenic factors on the accumulation and distribution of benzo[a]pyrene in soils has been established.